Genetic and kinetic basis of inorganic nutrient uptake in lichens - Gunawardhana, Pubudu L.T. (2017)
Lichens are self-sustaining entities formed by a symbiotic association between a fungal partner, the mycobiont, and a photosynthetic partner, the photobiont, which can be a green alga and/or a cyanobacterium. Lichens are amongst the most sensitive organisms to changes in environmental nutrient input and therefore nitrogen pollution frequently leads to modifications in lichen communities. Nitrogen enrichment is generally associated with a decrease in the frequency of species adapted to oligotrophic conditions and an increase in a relatively small number of species tolerant of high nutrient loadings. The present study aimed to understand how different lichen species might become adapted to nutrient poor and nutrient enriched habitats as well as gain insights into intra-specific responses towards nitrogen enrichment. For this purpose firstly, N and P uptake kinetics were compared in the eutrophication-tolerant lichen Xanthoria parietina and the eutrophication- sensitive species Cladonia portentosa. To evaluate the effect of N enrichment on Pi and NH4+ uptake, thalli of X. parietina from two locations with either relatively low or high rates of environmental N deposition were studied. Uptake of 33P-PO43-/HPO42- and 15N-NH4+ in both species followed Michealis – Menten kinetics in response to increasing substrate concentration. Xanthoria parietina from both locations had higher rates of Pi and NH4+ uptake than C. portentosa. Furthermore, data strongly indicated the presence of dual high and low affinity Pi uptake systems in both lichens. There was also evidence for dual affinity NH4+ uptake in Xanthoria parietina, but only single affinity uptake in C. portentosa. Secondly a bioinformatics approach was used to identify putative Pi and NH4+ transporter encoding genes. This was achieved via BLAST screening of draft genome sequences of X. parietina and C. portentosa constructed in collaboration with the Joint Genome Institute (USA) and Queens Medical Centre, Nottingham (UK). Putative high and low affinity Pi and NH4+ transporter encoding genes were identified from both model lichens, with a total of 20 candidate N and P transporter genes identified. Finally, a transcriptomic analysis was conducted to detect whether the candidate genes were expressed at mRNA level, thereby indicating potential functionality. This was coupled with investigation into whether the putative nutrient transporters displayed differential expression depending on the availability of N and P. Relative transcript levels of the candidate Pi and NH4+ transporter encoding genes were compared between X. parietina and C. portentosa collected from sites that were considered likely to differ in their degree of N enrichment. Intriguingly all the transporter encoding genes were expressed in all sample collections despite the variation in the degree of N enrichment in their habitats. Furthermore, results overall demonstrated a universal trend that increased N deposition is associated with lower expression of both high and low affinity Pi and NH4+ transporter encoding genes in both species. Thus, a combination of kinetic and genetic analysis of Pi and NH4+ uptake in the model lichens X. parietina and C. portentosa strongly indicates the presence of inter and intra-specific physiological and molecular responses towards the availability of key nutrients.